Solid/gas concentration measurements using multiple fan beam optical tomography - Abdul Rahim, R.; Leong, L.C; Chan, K.S.; Fazalul Rahiman, M. H.; Fang, J.F. (Bentham Open, 2008)
The application of optical sensors in process tomography involves using non-intrusive sensors to obtain vital information in order to produce images from the dynamic characteristics of a process system. Multiple fan beam projection technique here is defined as allowing more than one emitter to transmit light at the same time using the switch-mode fan beam method. For the thirty-two pairs of sensors used, the 2-projection technique and 4-projection technique are being investigated. Sixteen sets of projections will complete one frame of light emission for the 2-projection technique while eight sets of projection will complete one frame of light emission for the 4-projection technique. The data obtained from optical fibre sensors will then be reconstructed into image using the Linear Back Projection and Iterative Reconstruction algorithms through Visual C++ programming. Concentration measurements and series of error analyses will determine the feasibility of the optical fibre sensors to perform as an instrument in solid flow visualization.